Habits- A contemporary review - D R, Deepak; Shankar, Manu; B Nair, Karthika (International Journal of Dental Research, 2017)
Although oral habits are being dealt by dentist especially by Pedodontist and orthodontist since long time, but till today this particular ab-normal/normal entity is not fully known. Time-to-Time various hypothesis & explanations have been given by various authors but none of it specifically delineate the habits those which are normal for a particular age group and others, which are deleterious to stomatognathic sys-tem. The main reason for this difficulty is that a habit may be a part of normal development, a symptom associated with deep-rooted Psycho-logical disturbance or a habit may be a result of abnormal facial growth. Though it is difficult to delineate it, but it is important to have dif-ferentiation of abnormal from normal because If normal development get disturbed unknowingly and at the same time If abnormal growth or underlying psychological cause let continue without interfering at proper time/age it will lead to long lasting effect on stomatognathic system its growth & development and psychological development of child.